Genomic surveillance of Zika virus transmission in the Amazonas State, Brazil - Giovanetti, M; de Jesus, JG; Joshua, Q; Claro, IM; Xavier Junior, J; Hill, SC; Renato, S; Paz, P; Lourenço, J; Dellicour, S; Sabino, E; Loman, NJ; et al. (Oxford University Press, 2019)
Zika virus (ZIKV) has caused an unprecedented epidemic linked to severe congenital syndromes. Transmission of ZIKV in the Americas was first confirmed in May 2015 in northeast Brazil, though the virus was likely introduced 1–2 years prior to its detection. Manaus, the capital city of the Amazonas State, the largest territory of any state in Brazil and the main economic center in the northern region, reported between 2016 and 2017 more than 2,327 suspected cases of ZIKV infection. To gain insights into the timing, source, and likely route(s) of ZIKV introduction in the Amazonas State, we tracked the virus by sequencing ZIKV genomes from infected patients. Using nanopore sequencing technology, we generated 56 Brazilian ZIKV genomes from Manaus city in the Amazonas state, sampled from human cases. On the basis of available sequences of isolates from the Americas, the Manaus sequences, we analyzed fell within a single strongly supported monophyletic clade (bootstrap support = 99%, posterior support = 1.00) that belongs to the Asian genotype. Genetic analysis suggests the outbreak most likely originated from transmission cycles not previously identified in North Brazil and not from a separate introduction into the Americas. Molecular dating analysis indicates that the outbreak was caused by a single founder strain that is estimated to have arrived in Manaus around February 2015. By analyzing surveillance and genetic data, we discovered that ZIKV moved among transmission zones in Manaus. Geographical analysis further indicates that the Northern part of the Manaus regions has a high transmission potential for ZIKV. Our work illustrates that near-real time genomics in the field can augment traditional approaches to infectious disease surveillance and control. Estimated dates for the international spread of ZIKV from the north region indicate the persistence of the virus transmission in recipient regions. Our study provides an understanding of how ZIKV initiates transmission in new regions.